PENDAMPINGAN PEMANFAATAN AKUN MEDIA SOSIAL PADA PELAKU UMKM DI DESA REJOSO, KECAMATAN REJOSO, KABUPATEN NGANJUK Assintancing on create social media for UMKM in Rejoso Village, Rejoso sub-district, Nganjuk Regency, East Java Province - Imaningsih, Niniek; Fadil, Cholid; Meidianto, Chulaisy (Jurnal Ilmiah Wahana Pendidikan, 2023)
The development of technology from time to time is increasingly sophisticated, many new technologies have emerged to support human needs and facilitate the needs of human life, including UMKM players, UMKM players are facilitated to develop their products and businesses ranging from marketplaces, marketing sites, marketing applications and others. Marketing can be done through social media accounts with many users will be able to increase the income of UMKM businesses, one of which is the Instagram social media account, Instagram is a social media that is currently favored by the public because of its easy use and interesting application features, Instagram social media is no stranger because its popularity is worldwide.